Interleukin 6-regulated macrophage polarization controls atherosclerosis-associated vascular intimal hyperplasia - Chen, Jiaquan; Wang, Weilun; Ni, Qihong; Zhang, Lan; Guo, Xiangjiang (Frontiers in Immunology, 2022)
Vascular intimal hyperplasia (VIH) is an important stage of atherosclerosis (AS), in which macrophages not only play a critical role in local inflammation, but also transform into foam cells to participate into plaque formation, where they appear to be heterogeneous. Recently, it was shown that CD11c+ macrophages were more associated with active plaque progression. However, the molecular regulation of phenotypic changes of plaque macrophages during VIH has not been clarified and thus addressed in the current study. Since CD11c- cells were M2a-polarized anti-inflammatory macrophages, while CD11c+ cells were M1/M2b-polarized pro-inflammatory macrophages, we used bioinformatics tools to analyze the CD11c+ versus CD11c- plaque macrophages, aiming to detect the differential genes associated with M1/M2 macrophage polarization. We obtained 122 differential genes that were significantly altered in CD11c+ versus CD11c- plaque macrophages, regardless of CD11b expression. Next, hub genes were predicted in these 122 genes, from which we detected 3 candidates, interleukin 6 (Il6), Decorin (Dcn) and Tissue inhibitor matrix metalloproteinase 1 (Timp1). The effects of these 3 genes on CD11c expression as well as on the macrophage polarization were assessed in vitro, showing that only expression of Il6, but not expression of Dcn or Timp1, induced M1/M2b-like polarization in M2a macrophages. Moreover, only suppression of Il6, but not suppression of either of Dcn or Timp1, induced M2a-like polarization in M1/M2b macrophages. Furthermore, pharmaceutical suppression of Il6 attenuated VIH formation and progression of AS in a mouse model that co-applied apolipoprotein E-knockout and high-fat diet. Together, our data suggest that formation of VIH can be controlled through modulating macrophage polarization, as a promising therapeutic approach for prevent AS.